Preparation and characterization of iron complexes based on polysaccharides from agaricus bisporus - Cherno, Natalya; Osolina, Sophya; Nikitina, Olexandra (Eastern-European Journal of Enterprise Technologies, 2014)
According to WHO, correction and prevention of iron deficiency are one of the global problems of mankind. Under these conditions, the immune response dysfunction develops. Therefore, for the prevention and correction of iron deficiency it is advisable to use drugs and dietary supplements that combine antianaemia and immunomodulatory properties. This problem can be solved by preparing iron complexes based on polysaccharides of mushroom (Agaricus bisporus), in which β–(1→3)/(1→6)–D–glucans – active immunomodulators predominate. Complexes were prepared by mixing polysaccharide solution, separated from mushroom and ferric (III) chloride solution when heating. The pH value was adjusted by adding concentrated alkali solution. The mass ratio of iron: polysaccharides was varied from 1:0.25 to 1:3.00 by changing the polysaccharide solution concentration from 0.019 to 0.230 %. The possibility of preparing soluble iron complexes based on mushroom polysaccharides was shown. It was found that their yield and composition depend on the process conditions. The maximum yields of complexes with a high iron content can be obtained at a mass ratio of the inorganic and organic components of 1:1.0 at pH=12.0 and 1:2.5 at pH=8.5. Using IR and UV spectroscopy, gel filtration chromatography it was confirmed that the resulting products are nanosized complexes of polycyclic ferric hydroxide and mushroom polysaccharides. It is possible to predict the polyfunctional effects of produced iron complexes – along with antianemic, they can exhibit immunomodulatory activity. In Ukraine, analogs of such drugs are currently unknown, their further comprehensive study is of interest for both Nutritiology and Medicine.